A COMPARATIVE STUDY OF LONG-TERM OUTCOMES IN CHRONIC OBSTRUCTIVE PULMONARY DISEASES (COPD) AND ASTHMA PATIENTS RECEIVING INHALED CORTICOSTEROIDS - KHAN, RI; SATTI , SA; SHEEN , IN; AFRIDI, AU; ALI, K; KHALIQ, A (Biological and Clinical Sciences Research Journal, 2024)
Chronic obstructive pulmonary disease (COPD) is the fourth leading cause of death in most industrialized countries and affects about three million people worldwide. Objective: The primary objective of this study is to compare the long-term outcomes in patients with chronic obstructive pulmonary disease (COPD) and asthma who receive inhaled corticosteroids. Objective: To compare the long-term outcomes of inhaled corticosteroid (ICS) therapy in patients with chronic obstructive pulmonary disease (COPD) and asthma. Methods: This comparative, observational study was conducted at the Department of Pulmonology, Pak Emirates Military Hospital, a tertiary care center, from July 2024 to October 2024. A total of 230 patients participated in the study. Results: Data were collected from 230 patients. Asthma patients were younger (47.89 ± 12.02 years) compared to COPD patients (55.01 ± 10.23 years, p < 0.001) and had a higher proportion of females (70% vs. 30%, p < 0.001). Smoking history was more prevalent in COPD patients (85% vs. 10%, p < 0.001), reflecting its role as a primary risk factor. Asthma patients had a higher baseline BMI (25.5 ± 3.2 kg/m² vs. 23.8 ± 4.1 kg/m², p = 0.02) and shorter disease duration (8 ± 3 years vs. 12 ± 4 years, p < 0.01). Additionally, asthma patients had better baseline lung function (FEV1 68 ± 8% vs. 58 ± 10%, p < 0.001) and lower exacerbation rates (2.1 ± 0.5 vs. 3.2 ± 0.6 events/year, p < 0.001). The mean FEV1 improvement in asthma patients was 15% ± 3%, compared to 7% ± 2% in COPD patients (p = 0.01). Similarly, the FEV1/FVC ratio improved more in asthma patients (+12%) than in COPD patients (+5%, p = 0.01). Conclusion: It is concluded that inhaled corticosteroid (ICS) therapy significantly improves long-term outcomes in both asthma and Chronic Obstructive Pulmonary Disease (COPD) patients, but its effects are more pronounced in asthma.